The role of diversity in organizational resilience: a theoretical framework - Stephanie Duchek; Sebastian Raetze; Ianina Scheuch (Business Research, 2020)
Organizations today operate in an increasingly complex and turbulent world in which unexpected events are omnipresent. Thus, they need to develop resilience capabilities to manage unexpected disruptions, maintain high performance, and even thrive and grow. In research, there are preliminary indications that diversity could play an important role in the development of resilience in organizations. However, although there are numerous studies on both resilience and diversity, the connection between the two constructs remains largely unexplored. Our paper aims to narrow this research gap by answering the following questions: What role does diversity play in the development of organizational resilience? What does this mean for resilience-enhancing diversity management? To answer these questions, we link existing research on elements of organizational resilience and outcomes of diversity in organizations. By developing a theoretical framework, formulating propositions, and discussing implications for further research, this paper provides a foundation for future empirical research. Moreover, it offers useful insights into the successful management of organizational resilience.
Keywords: 650; Organizational resilience; Resilience capabilities; Diversity; Resilience-enhancing diversity management